2017
DOI: 10.5527/wjn.v6.i3.150
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological spectrum of snake bite-induced acute kidney injury from India

Abstract: AIMTo study the clinico-pathological spectrum of snake bite-induced acute kidney injury (AKI).METHODSA retrospective study of patients admitted at Indira Gandhi Medical College Hospital, Shimla with snake bite-induced AKI from July 2003 to June 2016. Medical records were evaluated for patient’s information on demographic, clinical characteristics, complications and outcome. Outcomes of duration of hospital stay, requirement for intensive care unit support, treatment with dialysis, survival and mortality were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
5
37
2
Order By: Relevance
“…Cortical necrosis in renal biopsy indicates poor prognosis and it is classically produced by the bite of Russell's viper. Similar findings were done by Vikrant et al 9 Delay in administration of ASV might be the reason for the development of renal lesions. 12 In this study, out of 19 patients with bite, wasp sting bite was seen in one patient and presented with renal failure with MODS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Cortical necrosis in renal biopsy indicates poor prognosis and it is classically produced by the bite of Russell's viper. Similar findings were done by Vikrant et al 9 Delay in administration of ASV might be the reason for the development of renal lesions. 12 In this study, out of 19 patients with bite, wasp sting bite was seen in one patient and presented with renal failure with MODS.…”
Section: Discussionsupporting
confidence: 79%
“…hospital was 3.4 days. 9 Kalantri et al noted mean bite to hospital time of 6.5±10.3 hours. 10 In our study out of 17 AKI in snake bites, hypotension occurred in only 3 patients and all three patients expired.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that 44% of patients with poisonous snakebites developed AKI. The reported prevalence rates of AKI following haemotoxic envenomation vary from 14 to 44% [ 4–8 , 15 ]. Relatively higher AKI prevalence rates have been reported by studies that have employed both urine output and creatinine-based criteria for the diagnosis of AKI, compared with studies that have employed creatinine-based criteria alone [ 5 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Envenomation is a common cause of community-acquired acute kidney injury (AKI) in tropical and subtropical areas, contributing to significant morbidity and mortality [ 2 , 3 ]. Even though AKI is a recognized complication of snakebite, the existing data concerning outcomes of AKI resulting from haemotoxic envenomation have been limited by retrospective study designs, a lack of uniformity in case definitions of AKI and limited follow-up [ 4–8 ]. The recent Kidney Disease: Improving Global Outcomes (KDIGO) definition and staging criteria have facilitated the early diagnosis of AKI, but the prognostic utility of these classification schemas in snakebite-related AKI is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Besides lethal effects snake envenomation also induces a wide range of local effects which can not be neutralized by anti serum. Nephropathy induced by snake venom was mentioned by Vikrant et al [ 1 ]. Histo-pathological examination showed intense dose and time dependent abnormalities, including swelling glomerulus and tubular necrosis and damage as well as signs of intertubular medullary hemorrhage at early stages of envenomation in kidney sections [ 2 ]· Viper envenomation is associated with degeneration and necrosis.…”
Section: Introductionmentioning
confidence: 99%